From helping to regulating – A transcriptomic profile of Ifng+ Il10+ Il21+ Cd4+ Th1 cells indicates their role in regulating inflammation during experimental trypanosomosis - Nguyen, Hang Thi Thu; Magez, Stefan; Radwanska, Magdalena (Frontiers in Tropical Diseases, 2023)
Trypanosoma evansi parasite infections cause a chronic animal wasting disease called Surra, and cases of atypical Human Trypanosomosis (aHT). In experimental models, T. evansi infections are hallmarked by the early onset of excessive inflammation. Therefore, balancing the production of inflammatory cytokines by anti-inflammatory IL-10 is crucial for prolonged survival. To improve the understanding of trypanosomosis induced immunopathology, we used scRNA-seq data from an experimental chronic T. evansi infection mouse model, resembling natural infection in terms of disease characteristics. For the first time, obtained results allowed to assess the transcriptomic profile and heterogeneity of splenic CD4+ T cell subsets, during a trypanosome infection. Here, the predominant subpopulation of T cells was represented by Tbx21(T-bet)+ Ccr5+ Id2+ type 1 helper T cells (Th1), followed by Icos+ Cxcr5+ Follicular T helper cells (Tfh) and very minor fraction of Il2ra(CD25)+ Foxp3+ regulatory T cells (Tregs). Interestingly, the profile of Th1 cells shows that besides Ifng, these cells express high levels of Il10 and Il21, coding for anti-inflammatory and immunoregulatory cytokines. This coincides with the elevated expression of key genes involved in IL-10 and IL-21 secretion pathway such as Stat1 and Stat3, as well as the transcriptional factors Prdm1 (Blimp 1), and Maf (c-Maf). In contrast, there is virtually no IL-10 transcription detected in the Treg population. Finally, differential gene expression and gene ontology analysis of infection-induced Ifng+ Il10+ Il21+ Th1 cells highlights their suppressive function on T cell activation, differentiation and INFɣ production itself. This indicates that during trypanosome infections, the Ifng+ Il10+ Il21+ Th1 cells, rather than Tregs, assume an immune regulatory role that is needed for dampening inflammation.